Effect of Saffron Extract on Proteins Biochemical Parameter of Serum - Modaresi, Mehrdad; Messripour, Manochehr; Asadi Marghmaleki, Mehran (Asian Journal of Chemistry, 2010)
Due to widespread use of saffron as food colourant and flavour and its reputation in folk medicine as a drug, this study was designed to assess the efficacy of saffron on serum proteins fractions in the male mice. Five group including eight adult male mice were used in this study. Normal saline administered as placebo to control group and saffron extract in doses of 25, 50, 100 and 200 mg/Kg/48 h were injected intraperitoneally for 20 days to the experimental groups. Albumin, α-1, α-2, β- and γ-globulins were separated electrophoretically and albumin/globulin ratio was calculated from the electrophoretogram. The result indicated that the levels of albumin increased significantly in two experimental groups that had received 50 and 100 mg/Kg/48 h of saffron extract as compared to that of control group. The levels of α-1 didn't have any remarkable changes in any group. The injection of saffron extract decreased (p < 0.05) the α-2 level in plasma as compared to the control group and levels of β-globulins increased significantly in these three groups. The levels of γ-globulins increased significantly in 100 and 200 mg/kgtreated groups as compared to the control group. Albumin/globulin ratio were significantly (p < 0.05) lower than control group in any groups that received saffron extract in a dose-dependent manner. Albumin were significantly increased in two groups and albumin/globulins ratio were decrease in any groups this can be interpreted that in the absence of antigen stimulation, serum globulins increased markedly by saffron. The study shows that since albumin synthesis occurs in the liver cells‚ thus administration of saffron may improve the status of liver function significantly.